Micronutrients in adult critically ill patients: lessons learned and the path toward precision - Christian Stoppe; Kursat Gundogan; Stefano Marelli (Current Opinion in Clinical Nutrition & Metabolic Care, 2026)
Purpose of review Despite strong biological plausibility, empiric high-dose micronutrient supplementation has failed to improve outcomes in critically ill patients. This review synthesizes evidence from the past 18 months and outlines the necessary transition toward biomarker-guided precision nutrition. Recent findings Recent evidence has further challenged routine high-dose micronutrient therapy. High-dose intravenous vitamin C failed to improve outcomes and was associated with potential harm in patients with sepsis, COVID-19, severe burns, and post-cardiac arrest syndrome. In contrast, a 2025 meta-analysis reported reduced short-term mortality and shorter ICU stay with vitamin D supplementation in patients on mechanical ventilation. Thiamine may shorten the duration of shock without affecting mortality. Observational studies suggest that carnitine deficiency is common during critical illness, and both deficiency and excess may be associated with adverse outcomes in critically ill patients. Selenium supplementation continues to show no clinical benefits in multiple sepsis phenotypes and high-risk surgical populations. Novel evidence also links trace element dysregulation to critical illness-acquired weakness, implicating copper-dependent cuproptosis, zinc homeostasis, and iron metabolism in the pathogenesis of muscle dysfunction. Advances in biomarkers (e.g. hepcidin, soluble transferrin receptor, ferritin, and selenoprotein P) are enabling more accurate identification of true deficiency states and targeted replacement strategies. Summary Current evidence does not support routine high-dose single-micronutrient therapy in critically ill patients and suggests potential harm with pharmacological doses of vitamin C. Clinicians should ensure that daily baseline requirements are met and reserve supplementation only for patients with biomarker-confirmed deficiency or biologically defined high-risk phenotypes. Future research should prioritize precision nutritional approaches based on validated biomarkers and individualized metabolic profiling.